C8-Substituted Imidazotetrazine Analogs Overcome Temozolomide Resistance by Inducing DNA Adducts and DNA Damage - Yang, Zhikuan; Wei, Danping; Dai, Xiaoli; Stevens, Malcolm F. G.; Bradshaw, Tracey D.; Luo, Ying; Zhang, Jihong (Frontiers in Oncology, 2019)
Temozolomide (TMZ) is the standard of care chemotherapeutic agent used in the treatment of glioblastoma multiforme. Cytotoxic O6-methylguaine lesions formed by TMZ are repaired by O6-methyl-guanine DNA methyltransferase (MGMT), a DNA repair protein that removes alkyl groups located at the O6-position of guanine. Response to TMZ requires low MGMT expression and functional mismatch repair. Resistance to TMZ conferred by MGMT, and tolerance to O6-methylguanine lesions conferred by deficient MMR severely limit TMZ clinical applications. Therefore, development of new TMZ derivatives that can overcome TMZ-resistance is urgent. In this study, we investigated the anti-tumor mechanism of action of two novel TMZ analogs: C8-imidazolyl (377) and C8-methylimidazole (465) tetrazines. We found that analogs 377 and 465 display good anticancer activity against MGMT-overexpressing glioma T98G and MMR deficient colorectal carcinoma HCT116 cell lines with IC50 value of 62.50 μM, 44.23 μM and 33.09 μM, 25.37 μM respectively. Analogs induce cell cycle arrest at G2/M, DNA double strand break damage and apoptosis irrespective of MGMT and MMR status. It was established that analog 377, similar to TMZ, is able to ring-open and hydrolyze under physiological conditions, and its intermediate product is more stable than MTIC. Moreover, DNA adducts of 377 with calf thymus DNA were identified: N7-methylguanine, O6-methylguanine, N3-methyladenine, N3-methylthymine and N3-methylcytidine deoxynucleotides. We conclude that C8 analogues of TMZ share a mechanism of action similar to TMZ and are able to methylate DNA generating O6-methylguanine adducts, but unlike TMZ are able at least in part to thwart MGMT- and MMR-mediated resistance.